2020
DOI: 10.1177/1557988320905407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serenoa repens With Tamsulosin in the Treatment of Benign Prostatic Hyperplasia: A Systematic Review and Meta-Analysis

Abstract: Studies reported that Serenoa repens was effective in relieving lower urinary tract symptoms (LUTS). This article carried out a systematic review and meta-analysis to compare Serenoa repens with tamsulosin in the treatment of benign prostatic hyperplasia (BPH) after at least 6-month treatment cycle. Four studies involving 1,080 patients (543 in the Serenoa repens group and 537 in the tamsulosin group) were included in the meta-analysis. The results were as follows: compared with tamsulosin, Serenoa repens had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
0
16
0
6
Order By: Relevance
“…Similarly, compared with tamsulosin [ 125 , 128 , 129 ], saw palmetto did not have a significant effect on PSA concentrations after 6 [ 128 ] and 12 [ 130 ] months of supplementation. Moreover, according to a recent Chinese meta-analysis [ 131 ], saw palmetto was more effective in reducing PSA concentrations among men with BPH as compared with tamsulosin; however, in this analysis, non-randomized trials were analyzed together with RCTs. Moreover, combined tamsulosin and saw palmetto therapy were also inefficient in reducing PSA compared with tamsulosin alone [ 129 ].…”
Section: Antioxidants and Psa Kineticsmentioning
confidence: 99%
“…Similarly, compared with tamsulosin [ 125 , 128 , 129 ], saw palmetto did not have a significant effect on PSA concentrations after 6 [ 128 ] and 12 [ 130 ] months of supplementation. Moreover, according to a recent Chinese meta-analysis [ 131 ], saw palmetto was more effective in reducing PSA concentrations among men with BPH as compared with tamsulosin; however, in this analysis, non-randomized trials were analyzed together with RCTs. Moreover, combined tamsulosin and saw palmetto therapy were also inefficient in reducing PSA compared with tamsulosin alone [ 129 ].…”
Section: Antioxidants and Psa Kineticsmentioning
confidence: 99%
“…Controversy data obtained from several previous reviews, data from early review stated that Saw Palmetto extract (Serenoa repens) alone, at double and triple doses, did not significantly decrease nightly urination on the AUA, peak urine flow, or prostate size in men with lower urinary tract symptoms consistent with BPH [3] . A study involving more than one thousand patients (55-80) years old with IPSS ≥ 7, to compare Saw Palmetto extract with tamsulosin in BPH therapy after at six month,also, Serenoa repens used for the same purpose due to it has the same effect in BPH therapy in terms of IPSS (p = 0.20), QoL (p = 0.33), Qmax (p = 0.21), PVR (p = 0.65), and PSA (p = 0.08) [12].…”
Section: Discussionmentioning
confidence: 99%
“…For adverse events, SPE was well tolerated compared with tamsulosin, especially in ejaculation disorders and libido decrease. 17 Wyatt et al pointed out that SPE may be a safe herbal supplement, even at a dose of 960 mg daily. 18 Moreover, a multicenter, randomized, double-blind, placebo-controlled trial performed by Zhang et al showed that SPE was effective and safe for the treatment of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS); only minor side effects such as nausea and stomach discomfort were observed.…”
Section: Safety and Toxicitymentioning
confidence: 99%